Characterization of bacteria from the rhizosphere of Som tree with multiple growth promoting traits - USHA CHAKRABORTY; BISHWANATH CHAKRABORTY, JINTU RABHA, DHRUVA KR. JHA*, HRIDIP KR. SARMA, AMRITA ACHARYA (Indian Phytopathology, 2014)
The present in vitro study was carried out to screen such beneficial rhizobacterial isolates that could be utilised for improvement of growth of som plant (Persea bombycina Kost.), a primary food source of the muga silkworm. Rhizobacteria was isolated from the rhizospheric soil collected from the som germplasm conservation site located at Regional Muga Research Station, Central Silk Board, Boko, Assam (GPS location 25.990 N, 91.250 E). Sixty-one percent of the total 18 isolates showed phosphate solubilisation as well as NH3 production. On the contrary, fewer isolates (33%) produced Indole Acetic Acid in vitro.Â Majority of the isolates showed resistance to Penicillin and Vancomycin at concentrations >10mcg. In addition, some of the isolates depicted antagonistic activity against Pestalotiopsis disseminata and Phyllosticta persea, the two phytopathogens responsible for causing grey blight and leaf spot diseases respectively in P. bombycina. Molecular identification of two potent plant growth promoting rhizobacteria (PGPR) isolates was carried out by amplification of their partial 16s rRNA and sequencing. NCBI BLAST search was done to find closest homologs. Sequences were submitted to GenBank and their phylogenetic tree construction was done with closely related standard sequences by DNA maximum likelihood method using MEGA5 software. Based on in vitro results, one PGPR isolate Pseudomonas sp. GUDBPKA301 was screened for in vivo study. A significant improvement in growth measured in terms of increase in shoot length, number of leaves and branches was observed when one year old Som saplings were bacterized under pot conditions. Results clearly suggest that Pseudomonas sp. GUDBPKA301 is a potential PGPR which can be used as an efficient microorganism for enhancement of plant growth in som cultivation.